2020
DOI: 10.1039/d0dt02642e
|View full text |Cite
|
Sign up to set email alerts
|

Increase of network hydrophilicity from sql to lvt supramolecular isomers of Cu-MOFs with the bifunctional 4-(3,5-dimethyl-1H-pyrazol-4-yl)benzoate linker

Abstract: The bifunctional linker 4-(3,5-dimethyl-1H-pyrazol-4-yl)benzoic acid (H2mpba) was used for the synthesis of new (square lattice) sql 2D metal-organic frameworks (MOFs) [Cu(Hmpba)2]∙L (L = DMF or ACN) in a solvent-mixture of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…40 The doubly deprotonated bifunctional pyrazolatecarboxylate ligand mpba 2− , constituting {Cu I 3 IJmpba) 3 } 3− , has already been used in the synthesis of a few reported coordination-bonded frameworks with other coordination bonded clusters, namely Zn II , [41][42][43] Co II 43 or Cu II . 16,44 It is also worth mentioning the reported, mostly 2D, structures of the partially deprotonated pyrazole-carboxylate ligand Hmbpa − with CoIJII), NiIJII), ZnIJII), CuIJII), CdIJII) 45 and the mixed-metal 1D bimetallic coordination polymer {[(Ti 3 O)IJiPro) 8 ]ijHmpba] 2 ijCu 2 -I 2 ] 0.5 } (with iPro = isopropoxide). 46 In the case of the mixedvalent Cu I/II framework compound of PCN-91 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…40 The doubly deprotonated bifunctional pyrazolatecarboxylate ligand mpba 2− , constituting {Cu I 3 IJmpba) 3 } 3− , has already been used in the synthesis of a few reported coordination-bonded frameworks with other coordination bonded clusters, namely Zn II , [41][42][43] Co II 43 or Cu II . 16,44 It is also worth mentioning the reported, mostly 2D, structures of the partially deprotonated pyrazole-carboxylate ligand Hmbpa − with CoIJII), NiIJII), ZnIJII), CuIJII), CdIJII) 45 and the mixed-metal 1D bimetallic coordination polymer {[(Ti 3 O)IJiPro) 8 ]ijHmpba] 2 ijCu 2 -I 2 ] 0.5 } (with iPro = isopropoxide). 46 In the case of the mixedvalent Cu I/II framework compound of PCN-91 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reasonable design along with creation of the MOFs is the present research hotspot. According to the literatures, it can be found that the structures and properties of MOFs are intimately related with the selected organic ligands [8–12]. In order to get the MOFs with desired structures and properties, we must carefully choose organic ligands having appropriate shape, symmetry, and coordination functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Structure-directing agents (SDAs) are becoming an active research area today, particularly in the fields of zeolite or molecular sieve syntheses. SDAs seldom appear in the final backbone of architectures but act as templates, space-filling molecules, or counterions for charge balance in the pores. Commonly used SDAs include organic/inorganic acids, polyoxometalatic acids, organic amines, and solvent molecules. Recently, SDAs began to be employed for the preparation of coordination polymers (CPs). , By analyzing previous works, we found that rational utilization of SDAs could result in different structures upon adjustment of the dimensions of CPs. …”
Section: Introductionmentioning
confidence: 99%